Dynamic metabolic profiling in vegetable soybean seed development - Guoqiang Lin, Runfang Hu (Emirates Journal of Food and Agriculture, 2018)
The edible quality of vegetable soybean is significantly associated with the number and type of metabolites. In the present study, metabolites in new vegetable soybean variety Mindou 6 at 49 to 67 days after flowering was investigated using gas chromatography coupled with mass spectrometry. The results showed that a total of 102 metabolites were identified from the vegetable soybean seeds, including 36 organic acids (35.3%), 21 amino acids, 11 polyols, 9 sugars, 7 phosphoric acids, 5 amines, 4 fatty acids, 4 nucleotides, and 5 other components. The principal component analysis indicated that the metabolites of amino acids, organic acids and sugars were greatly related to the quality of the vegetable soybean at the filling stages. A total of 40 differential metabolites were identified, including 14 amino acids, 13 organic acids and 2 sugars, and were found to be mainly involved in the metabolism of glycolysis, amino acids and phenylpropanoid. We systematically analyzed the change in the contents of metabolites in the developmental seeds of Mindou 6 and its effects on seed nutrition and eating quality. The suitable picking time was determined by combining the fresh pod yield and appearance quality. Taken together, these results can provide a theoretical reference for vegetable soybean breeding for high quality and efficient production.